N‐Terminal Labeling of Peptides by Trypsin‐Catalyzed Ligation for Quantitative Proteomics1. Issue 35 (5th July 2013) - Pan, Yanbo; Ye, Mingliang; Zhao, Liang; Cheng, Kai; Dong, Mingming; Song, Chunxia; Qin, Hongqiang; Wang, Fangjun; Zou, Hanfa
<x xml:space="preserve">Abstract</x> Two times an enzyme: Trypsin was first used as a protease to catalyze the digestion of proteins and then as a ligase to catalyze the linking of isotopically labeled amino acids to the N termini of tryptic peptides for quantitative proteomics. Reliable and accurate quantification of proteins was demonstrated for model proteins as well as proteome samples.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>